2013
DOI: 10.2337/db12-1363
|View full text |Cite
|
Sign up to set email alerts
|

Association of Ketone Body Levels With Hyperglycemia and Type 2 Diabetes in 9,398 Finnish Men

Abstract: We investigated the association of the levels of ketone bodies (KBs) with hyperglycemia and with 62 genetic risk variants regulating glucose levels or type 2 diabetes in the population-based Metabolic Syndrome in Men (METSIM) study, including 9,398 Finnish men without diabetes or newly diagnosed type 2 diabetes. Increasing fasting and 2-h plasma glucose levels were associated with elevated levels of acetoacetate (AcAc) and β-hydroxybutyrate (BHB). AcAc and BHB predicted an increase in the glucose area under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
117
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(128 citation statements)
references
References 40 publications
7
117
0
1
Order By: Relevance
“…Ketone bodies in blood are biomarker of energy source instead of diminished glucose utilities in diabetic hyperglycaemia 35, 36, which are high levels in individuals with diabetic hyperglycaemia 36 or in obese control relative to lean in DIO rat 37. Thus, this result suggested that SKL‐14959 might improve the glucose metabolism in peripheral tissues, resulted in decrease lipid deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Ketone bodies in blood are biomarker of energy source instead of diminished glucose utilities in diabetic hyperglycaemia 35, 36, which are high levels in individuals with diabetic hyperglycaemia 36 or in obese control relative to lean in DIO rat 37. Thus, this result suggested that SKL‐14959 might improve the glucose metabolism in peripheral tissues, resulted in decrease lipid deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Obese humans and mice exhibit diminished whole-body ketone body turnover (26,29). Furthermore, circulating ketone body concentrations are generally decreased in obese humans (24,25,27) and serve as predictive biomarkers for conversion to type 2 diabetes in patients with impaired fasting glucose (73). Compared with BMI-matched individuals, obese patients with NAFLD exhibit increased hepatic glucose production and TCA cycle flux without augmented ketogenesis (28).…”
Section: Discussionmentioning
confidence: 99%
“…2A and B). Dietary questionnaires, urinary excretion of pyrraline-an advanced glycation end product sourced only from food (21), and fasting plasma ketone body concentrations in the normal range in all subjects (22) suggested that food consumption was similar throughout the study (Table 2). Clinical safety indicators were normal at study entry and remained unchanged throughout the placebo and tRES-HESP treatment periods (Supplementary Table 1).…”
Section: Improved Clinical Metabolic and Vascular Health With Tres-hementioning
confidence: 99%